Leptin is Associated with the Tri-Ponderal Mass Index in Children: A Cross-Sectional Study - Empringham B; Jennings WJ; Rajan R; Fleming AJ; Portwine C; Johnston DL; Zelcer SM; Rassekh SR; Tran V; Burrow S; Thabane L; Samaan MC (Dove Medical Press, 2021)
Brianna Empringham,1,2 William J Jennings,1,2 Raeesha Rajan,1– 3 Adam J Fleming,1,4 Carol Portwine,1,4 Donna L Johnston,5 Shayna M Zelcer,6 Shahrad Rod Rassekh,7 Victoria Tran,1,2 Sarah Burrow,8 Lehana Thabane,3,9– 11 M Constantine Samaan1– 3 1Department of Pediatrics, McMaster University, Hamilton, Ontario, Canada; 2Division of Pediatric Endocrinology, McMaster Children’s Hospital, Hamilton, Ontario, Canada; 3Department of Health Research Methods, Evidence and Impact, McMaster University, Hamilton, Ontario, Canada; 4Division of Pediatric Hematology/Oncology, McMaster Children’s Hospital, Hamilton, Ontario, Canada; 5Division of Pediatric Hematology/Oncology, Children’s Hospital of Eastern Ontario, Ottawa, Ontario, Canada; 6Pediatric Hematology Oncology, Children’s Hospital, London Health Sciences Center, London, Ontario, Canada; 7Division of Pediatric Hematology/Oncology/BMT, Department of Pediatrics, British Columbia’s Children’s Hospital, Vancouver, BC, Canada; 8Division of Orthopedic Surgery, Department of Surgery, McMaster University Medical Centre, Hamilton, Ontario, Canada; 9Department of Anesthesia, McMaster University, Hamilton, Ontario, Canada; 10Centre for Evaluation of Medicines, St. Joseph’s Health Care, Hamilton, Ontario, Canada; 11Biostatistics Unit, St Joseph’s Healthcare-Hamilton, Hamilton, Ontario, CanadaCorrespondence: M Constantine SamaanDepartment of Pediatrics, McMaster University, Division of Pediatric Endocrinology, McMaster Children’s Hospital, 1280 Main Street West, 3A-57, Hamilton, Ontario, L8S 4K1 Tel +001-905-521-2100, ext. 75926Fax +001-905-308-7548Email samaanc@mcmaster.caBackground: Obesity is characterized by the disproportionate expansion of the fat mass and is most commonly diagnosed using the Body Mass Index (BMI) z-score or percentile in children. However, these measures associate poorly with the fat mass. This is important, as adiposity is a more robust predictor of cardiometabolic risk than BMI-based measures, but there are limited clinical measures of adiposity in children. A new measure, the Tri-ponderal Mass Index (TMI, kg/m3) has recently demonstrated robust prediction of adiposity in children. The aim of this study is to explore the association of leptin, a validated biomarker of the fat mass, with TMI.Methods: One hundred and eight children and adolescents were included in this cross-sectional study. Height and weight were used to calculate TMI. Plasma leptin was measured using ELISA. Multivariable regression analysis was applied to determine the predictors of TMI.Results: The age range of participants included in this study was 8.00– 16.90 years (female n=48, 44%). Leptin correlated with BMI percentile (r=0.64, p-value < 0.0001) and TMI (r=0.71, p-value < 0.0001). The multivariable regression analysis revealed that BMI percentile (Estimated Beta-coefficient 0.002, 95% CI 0.002– 0.003, p-value < 0.0001) and Leptin (Estimated Beta-coefficient 0.05, 95% CI 0.02– 0.07, p-value 0.013) were associated with TMI.Conclusion: Leptin is associated with TMI in healthy children. The TMI is a feasible clinical measure of adiposity that may be used to stratify children and adolescents for further assessments and interventions to manage and attempt to prevent cardiometabolic comorbidities.Keywords: Tri-ponderal mass index, adiposity, leptin, children